Reattachment of fractured anterior tooth fragment: An approach in endo esthetic view (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Esthetic rehabilitation of crown fractured anterior teeth is one of the greatest challenges to the dental specialists in concern of long-term biological function. Traditional views demonstrate limitations with much controversy in MICD (Minimally invasive cosmetic dentistry) concept. To meet the challenge a new biological approach in endo esthetic view is considered. This case report represents the management of a fractured right maxillary central incisor tooth of 27 year-old-male patient where his own fractured tooth fragment restored by reattachment technique. The clinical examination revealed complicated crown fracture extended horizontally from mesial to distal and angulated incisally from palatal to labial with pulp exposure. The fracture was not evident labially. In this case, the procedure was used to repair the fracture tooth fragment included root canal treatment and glass fiber post for reinforcement. The tooth fragment was luted with light activated flowable composite resin.  Onward assessment showed a stable reattachment, good esthetic and function with healthy periodontium.